1999
DOI: 10.1063/1.480017
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron scattering by H2O, H2S, H2Se, and H2Te

Abstract: Articles you may be interested in Dissociative recombination of H + ( H 2 O ) 3 and D + ( D 2 O ) 3 water cluster ions with electrons: Cross sections and branching ratiosWe report elastic differential, integral, and momentum transfer cross-sections for H 2 X molecules ͑X: O, S, Se, and Te͒ obtained at the static exchange level of approximation. The energy range considered was from 2 up to 30 eV for H 2 O and from 5 up to 30 eV for the other molecules. Our calculations were performed with the Schwinger multicha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 40 publications
4
27
1
Order By: Relevance
“…Solid line (black), present TCS using the Qmol formaliam); dash line (blue), recent TCS using the SCOP formalism; stars, experimental results of Zecca et al [9]; open diamonds, experimental results of Szmytkowski et al [22]; open circles, experimental results of Jones et al [5]; filled squares, experimental results of Gulley et al [20]. [27]; light pink dotted line, theoretical data of Gupta and Baluja [24]; dash-dot-dot line, theoretical data of Jain and Baluja [26]; long dash-dot line, theoretical data of Varella et al [23]; short-dash-dot, theoretical data of Lengsfield et al [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid line (black), present TCS using the Qmol formaliam); dash line (blue), recent TCS using the SCOP formalism; stars, experimental results of Zecca et al [9]; open diamonds, experimental results of Szmytkowski et al [22]; open circles, experimental results of Jones et al [5]; filled squares, experimental results of Gulley et al [20]. [27]; light pink dotted line, theoretical data of Gupta and Baluja [24]; dash-dot-dot line, theoretical data of Jain and Baluja [26]; long dash-dot line, theoretical data of Varella et al [23]; short-dash-dot, theoretical data of Lengsfield et al [25].…”
Section: Resultsmentioning
confidence: 99%
“…Electron-impact total cross sections for H 2 S have been measured at low energies by Jones et al (0.02-10 eV) [5], Gulley et al (1-30 eV) [20], and Sokolov and Sokolova (0-10 eV) [21], and at low to high energy by Szmytkowski et al (6-370 eV) [22] and Zecca et al (75-4000 eV) [9]. Low-energy calculations were carried out by Varella et al (5-30 eV) [23] using the Schwinger multichannel method and by Gupta and Baluja (0.025-15 eV) [24] using the R-matrix code. Lengsfield et al [25] have also reported data in the energy range 1-30 eV.…”
Section: Introductionmentioning
confidence: 99%
“…(51)). For high-symmetry target molecules [55,56] an advantage may be taken from rotational selection rules, so this procedure can be stated on more rigorous grounds (see Sect. 2.2.5).…”
Section: Born-closure Correctionsmentioning
confidence: 99%
“…First, equation (55) provides a means to estimate the rotational excitation cross sections (for any Γ → Γ transition, not only from the ground state). Second, the RSDCS in equation (57) is particularly useful for highly symmetric targets [55,56] that impose stringent selection rules for dipole-allowed 0 → Γ rotational excitations. As a result, the Born-closure procedure (Eq.…”
Section: Adiabatic Excitation Cross Sectionsmentioning
confidence: 99%
“…Experimental elastic differential cross sections (DCSs) for electron scattering from water have been known for some time [6] and are commonly used in track structure simulations. Only recently have measurements appeared concerning more complex biological molecules, such as formic acid [7], variations of the tetrahydrofuran ring [8,9], alanine [10], and pyrimidine [11].…”
Section: Introductionmentioning
confidence: 99%